2016
DOI: 10.1177/1077801216646223
|View full text |Cite
|
Sign up to set email alerts
|

Intersections of Race, Ethnicity, and Gender

Abstract: Using an intersectional framework, this article discusses the barriers to social services that Latina victims of intimate partner violence encounter, a drastically underdeveloped area of theorizing. We argue that placing Latinas at the center of analysis will facilitate empirical knowledge, which is necessary because mainstream inquiry has historically ignored their interests. First, we discuss cultural barriers through the lenses of gender, race, and ethnicity. Second, we describe socioeconomic barriers in co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(36 citation statements)
references
References 108 publications
(164 reference statements)
1
27
0
Order By: Relevance
“…A large body of literature demonstrates that the immigrant population in the US has limited access to formal resources such as social, legal, and health services, as well as basic human and social capital resources (Fuchsel & Murphy, 2012;O'Neal & Beckman, 2016;Runner et al, 2009).…”
Section: Literature Reviewmentioning
confidence: 99%
“…A large body of literature demonstrates that the immigrant population in the US has limited access to formal resources such as social, legal, and health services, as well as basic human and social capital resources (Fuchsel & Murphy, 2012;O'Neal & Beckman, 2016;Runner et al, 2009).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The history of radical thinking and practice in the battered women's movement has shown that domestic violence is not an incident-based, criminal-legal issue, but rather a social problem with deep roots in historical systems of social domination and institutional oppression not only on the basis of sex/gender, but also the intersection of race, social class, age, and other variables (Dobash & Dobash, 1992, 1998Yllo & Bograd, 1988). Despite an ever-expanding domestic violence service industry, literature and informal reports affirm that survivors who are BIPOC continue to be under/ poorly served by mainstream anti-violence agencies (Bent-Goodley, 2005;Kulkarni, 2019;O'Neal & Beckman, 2017).…”
Section: The Build-up Of the Domestic Violence Service Industrymentioning
confidence: 99%
“…Minority couples are two to three times more likely to report intimate partner violence (IPV) than Caucasian couples (Caetano et al, 2005). However, minority women are less likely than Caucasian women to use social services, battered women's programs, or seek help from health care professionals (O'Neal & Beckman, 2017;National Resource Center on Domestic Violence, 2006).…”
Section: Risk Factors Of Gun Violencementioning
confidence: 99%